2017
DOI: 10.22555/joeed.v4i1.982
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Rote Learning on High and Low Achievers in Graduate and Undergraduate Programs

Abstract: <p>A survey was conducted to study the preferred learning strategies; that is, surface learning or deep learning of undergraduate and graduate male and female students and the impact of the preferred strategy on their academic performance. Both learning strategies help university students to get good scores in their examinations to meet the demands of industry in workforce. Quantitative research method was used to determine the impact of learning strategy on academic achievements. The R-SPQ2F questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…High and low successful student both favor deep learning approach (Ahmed & Ahmad, 2017). Students with high achievement showed high feeling of academic self -efficacy (Lavadores, Escobeda, & Sosa, 2017).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…High and low successful student both favor deep learning approach (Ahmed & Ahmad, 2017). Students with high achievement showed high feeling of academic self -efficacy (Lavadores, Escobeda, & Sosa, 2017).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Another important point to note in terms of gender differences is the use of a surface approach, better known as rote learning, especially among girls. Ambreen and Nawaz (2017) subsequently criticized Western education that has a negative opinion of rote learning. They commented on the essentials of rote learning in Eastern society, and that as such, skills support deeper understanding and critical thinking.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the role of learning approaches in explaining gender differences, it was found that the girls outperformed boys in terms of the surface approach to learning (Byrne et al, 2002;Hassal & Joyce, 2001) despite Koh and Koh's (1999) study that claimed that the boys in their study utilized the surface approach more than girls. A recent comparative study conducted in two Pakistani universities by Ambreen and Nawaz (2017) showed that there were no differences in the learning approaches of boys and girls while Ahmed, Ahmed, Waheed, Shoaib and Khan (2014) and Lie and Angelique (2007) contended that the boys used more deep approaches. A meta-analysis by Severians and Dam (1994) on 26 studies focused on learning approaches concluded that girls learn for the sake of learning while boys prefer abstraction and conceptualization.…”
Section: Gender Differences In Generic Skills and Learning Approachesmentioning
confidence: 99%
“…Science programs ought to have a structure that encourages and guides future teachers to feel responsible for educating themselves, participating actively in the learning process, and transforming their findings into results. A good approach to learning inculcated in trainees represents an important factor that contributes to achieving the stated goals of science education (MoNE, 2018; Ahmed and Ahmad, 2017) [47,52]. According to Asubel (1963) [53], a learning approach is described as (1) meaningful and (2) via rotelearning.…”
Section: Science Process Skills and Meaningful Learningmentioning
confidence: 99%